ṬAWĀF AL-MAR’AH AL-ḤĀ’ID FI AL-MANẒAR AL-ISLĀMIY: DIRĀSAH MUQĀRANAH BAYN AL-MADHĀHIB AL-FIQHIYYAH AL-ISLĀMIYYAH - hudzaifah achmad qotadah; Adang Darmawan Achmad (Islam Futura, 2021)
One of the most important tasks in performing an obligation of worship is that a servant is required to learn the law as it was formed by sharia and religion, so that he could worship properly. Hajj is one of Islam's pillars where Islamic law requires all followers to run it for those who have the ability, even if only once in their lifetime, as He has said in the al-Qur’an: “Pilgrimage thereto is a duty men owe to Allah,- those who can afford the journey; but if any deny faith, Allah stands not in need of any of His creatures.” (QS: Al-Imran: 97). There are requirements in carrying out the Hajj and Umrah which should be fulfilled in their completion as a servant must manage, understand, etc. There are obligations to be performed in the conduct of Hajj and Umrah, and one is Ihram, Ramy al-Jamarat, stay a night in muzdalifah and so on. Furthermore, in the act of performing hajj and umrah there have been several pillars that must be performed such as tawaf. While as far as tawaf is concerned, there is an interesting discussion among many of the scholars on the issue of tawaf during Hajj and Umrah where it would be required to remain to purify during the hajj and umrah especially for a women within her menstruation cycle.